A bibliography on the analytical model of the mechanical behaviour in uniaxial tension of fibre concrete: Application to concrete reinforced with fibres and powders from recycling of thermoset composite materials. (30th January 2017) - Benzerzour, Mahfoud; Sebaibi, Nassim; Maherzi, Walid; Abriak, Nor Edine; Sebaibi, Yahya
Highlights: Local bending of fibres at an angle β increases the stability of fibres to pullout. The tensile strength of FRCs is obtained with a fibre orientation from 42° to 55°. The best post-peak response would be obtained with an orientation of 42–55°. Abstract: This article presents a qualitative and quantitative observation of composite rupture under uniaxial tension and analytical modelling of behaviour under uniaxial tension. The chapter begins with a bibliographic review of the numerical and analytical models in the literature. Then follows an analysis of rupture processes during tension testing in order to define an analytical model for softening (or post peak) behaviour of Fibre and Powder Reinforced Concrete (FPRC). Modelling is at meso-level, taking into account fibre-matrix interactions and their number and orientation through crack(s) as basic parameters. The modelling is applied to 11.54% fibre and powder reinforced concretes. Powders are considered as short fibres 400 μm long.